(1501) An information system for personal management system Using advanced techniques of DBASE III PLUS نظام معلومات لإدارة شؤون الموظفين باستخدام تقنيات متقدمة من DBASE III PLUS - El-Daoushy, Abdalla; Youssef, Yehia (The Institute of National Planning, 2018)
This memo. is divided into two main parts of three chapters. Part one which comprises chapter 1 discusses the programming considerations and emphasize on advanced techniques for maximizing the speed and performance of designing and building software systems. Part two comprises chapters 2 and 3 and presents a custom software system for managing a Personnel Management System. The techniques presented in designing this software system can be used to manage any single dataBase system.